Genomic Characterization of the Arsenic-Tolerant Actinobacterium, Rhodococcus Erythropolis s43 - Levican-Jaque, G (Trans Tech Publications Ltd, 2017)
Rhodococcus erythropolis S43 is an actinobacterium isolated from an arsenic-contaminated soil sample, collected from an old smelter site, including an arsenic smelter, in Germany. This strain has unique features as compared to the other members of the species, namely resistance to elevated concentrations of arsenic. Here, we present the microbiological features and genomic properties of this biotechnologically relevant strain. The 6,812,940 bp draft genome is arranged into 264 scaffolds of 848 contigs. It possesses 62.5% of CG content and comprises 6,040 coding sequences and 49 tRNA genes. Bioinformatic genome analysis showed the presence of arsenic-resistance genes. A complete ars operon was found containing the arsACDR cluster coding for ArsA (efflux pump ATPase), ArsC (arsenate reductase), ArsD (chaperone) and ArsR (ars operon regulator). Our results show that the arsC mRNA level significantly increased in response to arsenite and arsenate exposure, suggesting its involvement in the arsenic resistance phenotype of strain S43. In addition, this strain showed to have a plethora of genes coding for proteins involved in oxidative-stress response, including catalase, super-oxide dismutase, glutathione peroxidase-related genes, thioredoxin and thioredoxin reductase, suggesting it is highly tolerant to oxidative conditions. Finally, genes for radiation resistance, biodesulfurization, and oil and phenol degrading pathways were also detected. Altogether this data make R. erythropolis S43 a good candidate microorganism for bioremediation of highly contaminated environments and other industrial applications. © 2017 Trans Tech Publications, Switzerland.